2016
DOI: 10.3389/fphys.2016.00571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Endothelial Vasomotor Function

Abstract: The endothelium plays an important role in the regulation of vasomotor tone and the maintenance of vascular integrity. Endothelial dysfunction, i.e., impaired endothelial dependent dilation, is a fundamental component of the pathogenesis of cardiovascular disease. Although endothelial dysfunction is associated with a number of cardiovascular disease risk factors, those risk factors are not the only determinants of endothelial dysfunction. Despite knowing many molecules involved in endothelial signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…A portion of data presented here is reproduced from our previous publish (Kim et al . Front Physiol 2016;7:571 [16]).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of data presented here is reproduced from our previous publish (Kim et al . Front Physiol 2016;7:571 [16]).…”
Section: Figmentioning
confidence: 99%
“…We and others showed that EDR is determined by genetic background in mice [101112]. In humans, the estimated heritability of FMD ranges from 0.14 to 0.44 [13141516], suggesting that up to 45% of the variation in FMD is due to genetic factors. Others also reported that changes in FMD in response to training are more correlated in monozygotic than dizygotic twins [1718], implying that endothelial responses to exercise training are also partially affected by genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, this was the first study to report that the atherosclerotic process previously observed in coronary arteries also involves the peripheral vessels in HAE patients. Nitric oxide production impairment, through the still poorly-understood bradykinin receptor-ADMA pathway activation, was hypothesized to be involved (Rastaldo et al, 2007 ; Kim and Massett, 2016 ; Wang et al, 2016 ). This may indicate a much more extensive hardening of the arteries, involving the entire arterial tree.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the pathophysiology of CSFP is not exact; it is thought to be caused by various causes in blood vessels, in the form of coronary microvascular disease, inflammation and endothelial dysfunction [9], [10], [11]. The pathogenesis of CSFP also involves a vital role of the renin-angiotensin-aldosterone system (RAAS).…”
Section: Introductionmentioning
confidence: 99%
“…This system consists of hormones and enzymes, which include angiotensinogen, angiotensin-converting enzyme (ACE), angiotensin I (AT1), angiotensin II (AT2), and aldosterone. AT2 has two receptor subtypes, namely, type 1 receptor (AT1R) and type 2 receptors (AT2R) [10]. The function of AT2 not only to stimulating aldosterone secretion but also to constrict blood vessel, stimulates various growth factors, initiates hypertrophy and smooth muscle hyperplasia of blood vessels, making the condition of arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%